HUBUNGAN PENGGUNAAN BEDAK BAYI USIA 0-9 BULAN PAD AREA GENETALIA DENGAN KEJADIAN DIAPER RASH (RUAM POPOK) DI RUMAH BERSALIN ZOHYA PERBAUNGAN TAHUN 2023 - Paninsari, Debora; Khoir, Umul; Yunita, Rini Sandra; Oktavia, Rini Firdayeni; Pohan, Rini Astuti; Amdani, Riska (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2024)
Babies with relatively vulnerable skin often suffer from skin problems, because the baby's skin is very delicate, making babies very dangerous for health disorders, infections and serious threats. Among the skin problems that often arise include diaper rash (diaper rash). Part of the trigger for diaper rash is the use of powder in infants, which causes extreme itching. This research implements a cross-sectional strategy to summarize the same timely information on intersubject engagement with group comparisons set on specific traits. The discovery was implemented at Zohya Perbaungan Maternity Home, out of 30 babies exposed to 25 babies suffering from diaper rash (diaper rash) mostly triggered by the use of baby powder. Corresponding chi-square test describes p- value= 0.000 where ? 0.05 displays 0.000<0.05, thus HI approved H0 was canceled which revealed emerging association of 0-9 month old infant powder use in Genetalia area with incidence of diaper rash (diaper rash) in Zohya Perbaungan Maternity Home.